Cancer‐testis antigen ACRBP expression and serum immunoreactivity in ovarian cancer: Its association with prognosis. Issue 4 (16th September 2021) - Lin, Lina; Nong, Weixia; Luo, Bin; Ge, Yingying; Zeng, Xia; Li, Feng; Fan, Rong; Zhang, Qingmei; Xie, Xiaoxun
Abstract: Introduction: Cancer testis (CT) antigens are attractive targets for cancer immunotherapy because of their expression restriction and immunogenicity. The acrosin binding protein (ACRBP) is a member of CT antigens. This study aimed to evaluate ACRBP expression and immunogenicity in ovarian cancer (OC). Methods: The expression level of ACRBP in OC tissues, normal ovarian tissues, and cell lines was detected via quantitative real‐time polymerase chain reaction (qRT‐PCR) and immunohistochemistry. We determined the levels of ACRBP antigen and antibody in serum samples collected from patients with OC and healthy donors using enzyme‐linked immunosorbent assays (ELISA), the level of ACRBP in cell‐cultured medium was also tested. Results: ACRBP mRNA and protein expressions were upregulated in OC tissues relative to normal tissue, especially highly expressed in epithelial ovarian cancer (EOC). Moreover, ACRBP expression was significantly correlated with International Federation of Gynecology and Obstetrics (FIGO) stage and chemosensitivity. Serological analysis showed that anti‐ACRBP antibody was detected in the sera of 16 of the 56 (28.5%) patients with OC but not in healthy donors. The area under the receiver operating characteristic curve for ACRBP antibody was 0.802 (95% confidence interval [CI]: 0.708–0.876), and the sensitivity and specificity for ACRBP antibody was 85.71% and 55.0%, respectively. Kaplan–Meier analysis revealed that the overall survival (OS) and disease‐free survival (DFS) in OC patients with high ACRBP expression were significantly lower than those with low expression ( p = 0.040, p = 0.021). However, ACRBP antibody level was not associated with prognosis. Conclusion: ACRBP expression was upregulated in OC tissues and induced humoral immune response in patients with OC, suggesting that ACRBP is a potential prognostic biomarker and a target of tumor immunotherapy for OC. Abstract : (1) Acrosin binding protein (ACRBP) was a restricted expression cancer‐testis antigen in cancers. Its expression was markedly upregulated in ovarian cancer tissues and induced humoral immune response in patients with ovarian cancer. Serological detection of ACRBP had high sensitivity in ovarian cancer. (2) The overexpression of ACRBP was associated with advanced stage of tumor, metastasis, and chemoresistance in ovarian cancer. High ACRBP expression was associated with a poor clinical outcome. (3) ACRBP also displayed inherent immunogenicity. Together with its restricted expression pattern and high specificity to cancer cells, ACRBP could be a potential target for prognostic evaluation and tumor‐specific antigen‐based immunotherapy for patients with ovarian cancer.